Prenatal maternal stress and birth outcomes in rural Ghana: sex-specific associations - Kenneth Ayuurebobi Ae-Ngibise; Blair J. Wylie; Ellen Boamah-Kaali; Darby W. Jack; Felix Boakye Oppong; Steven N. Chillrud; Stephaney Gyaase; Seyram Kaali; Oscar Agyei; Patrick L. Kinney; Mohammed Mujtaba; Rosalind J. Wright; et al. (BMC, 2019)
Abstract Background In developed countries, prenatal maternal stress has been associated with poor fetal growth, however this has not been evaluated in rural sub-Saharan Africa. We evaluated the effect of prenatal maternal stress on fetal growth and birth outcomes in rural Ghana. Methods Leveraging a prospective, rural Ghanaian birth cohort, we ascertained prenatal maternal negative life events, categorized scores as 0-2 (low stress; referent), 3-5 (moderate), and > 5 (high) among 353 pregnant women in the Kintampo North Municipality and Kintampo South District located within the middle belt of Ghana. We employed linear regression to determine associations between prenatal maternal stress and infant birth weight, head circumference, and length. We additionally examined associations between prenatal maternal stress and adverse birth outcome, including low birth weight, small for gestational age, or stillbirth. Effect modification by infant sex was examined. Results In all children, high prenatal maternal stress was associated with reduced birth length (β = − 0.91, p = 0.04; p-value for trend = 0.04). Among girls, moderate and high prenatal maternal stress was associated with reduced birth weight (β = − 0.16, p = 0.02; β = − 0.18, p = 0.04 respectively; p-value for trend = 0.04) and head circumference (β = − 0.66, p = 0.05; β = − 1.02, p = 0.01 respectively; p-value for trend = 0.01). In girls, high prenatal stress increased odds of any adverse birth outcome (OR 2.41, 95% CI 1.01-5.75; p for interaction = 0.04). Sex-specific analyses did not demonstrate significant effects in boys. Conclusions All infants, but especially girls, were vulnerable to effects of prenatal maternal stress on birth outcomes. Understanding risk factors for impaired fetal growth may help develop preventative public health strategies. Trial registration NCT01335490 (prospective registration). Date of Registration: April 14, 2011. Status of Registration: Completed.